2021
DOI: 10.1007/s11845-021-02798-7
|View full text |Cite
|
Sign up to set email alerts
|

Video analysis of potential concussions in elite male Hurling: are players being assessed according to league guidelines?

Abstract: Background Hurling is a fast-paced contact sport that places players at risk of concussion. Given the consequences of repeated concussive impacts, it is imperative that concussion management guidelines are followed. Hypothesis/Purpose. The aim of this study is to determine if potential concussive events (PCEs) in elite Hurling are assessed in accordance with league management guidelines. The secondary objective is to investigate the effectiveness of current concussion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This study also found that 25/182 players experiencing a PCE returned to play without any assessment, while most assessments were under 1 min. 84 These practices, along with the high SRC rates found in ladies’ Gaelic football and camogie and the low levels of data collection in our study, highlight a gap in the literature that should be addressed by future research.…”
Section: Discussionmentioning
confidence: 75%
“…This study also found that 25/182 players experiencing a PCE returned to play without any assessment, while most assessments were under 1 min. 84 These practices, along with the high SRC rates found in ladies’ Gaelic football and camogie and the low levels of data collection in our study, highlight a gap in the literature that should be addressed by future research.…”
Section: Discussionmentioning
confidence: 75%
“…Reviewers were trained in video analysis at the injury prevention lab at St Michael’s Hospital in Toronto, Ontario, Canada, and have previously published PCE research in international soccer and Gaelic football. [ 12 , 15 , 16 , 21 , 22 ] Match footage was retrieved from the GAAGO online streaming service and was analyzed using QuickTime Player v10.5 (which enables frame-by-frame viewing). No patient data was utilized for this study, and all footage is public domain.…”
Section: Methodsmentioning
confidence: 99%
“…Various steps have been taken to improve concussion assessment practices, such as the implementation of the GAA concussion management guidelines and, more recently, the announcement of a concussion interchange rule [ 14 ]. We have discussed this in previous papers on both Gaelic football and hurling [ 12 , 15 ]. However, these measures do little to reduce the primary incidence or severity of concussion.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation